Effect of chemoradiotherapy on the dynamics of circulating lymphocyte subsets in patients with non-metastatic nasopharyngeal carcinoma - Lilan Yi; Lilan Yi; Yinfang Gu; Yinfang Gu; Longhua Guo; Longhua Guo; Xiaofang Zou; Xiaofang Zou; Guowu Wu; Guowu Wu (Frontiers in Oncology)
BackgroundChemoradiotherapy (CRT) is the primary and most effective treatment for non-metastatic nasopharyngeal carcinoma (NPC), exerting antitumor effects by modulating immune cells. Distinct subpopulations of immune cells exhibit specific sensitivity to CRT. This study aimed to characterize the dynamics of the proportions and absolute counts of peripheral circulating lymphocyte subsets in non-metastatic NPC before and after CRT, and to elucidate their association with clinical responses.MethodsA total of 91 patients with non-metastatic NPC were enrolled. Flow cytometry was employed to detect the expression of CD3, CD4, CD8, CD56, and CD19 on peripheral blood cells. The composition of lymphocyte subsets before treatment, post-completion of CRT, and one month following CRT was retrospectively analyzed. Further, the relationship between the composition of circulating lymphocyte subpopulations and distinguish clinical responses was evaluated.ResultsThe proportion of CD3+ T cells showed an initial increase followed by a significant decrease at baseline, post-completion of CRT, and one month following CRT. The proportions of CD3+CD4+ T cells, CD4+/CD8+ ratio, and CD19+ B cells continued to decline at baseline, post-completion of CRT, and one month following CRT, while the proportions of CD3+CD8+ T cells and CD16+CD56+ NK cells progressively increased. The absolute counts of circulating lymphocyte subsets, including CD3+ T cells, CD3+CD4+ T cells, CD3+CD8+ T cells, CD45+, CD19+ B cells, and CD16+CD56+ NK cells, demonstrated a trend of initial decrease followed by an increase at baseline, post-completion of CRT, and one month following CRT. Patients with complete response (CR) and partial response (PR) presented similar dynamic trends in the percentages and absolute counts of circulating lymphocyte subpopulations at baseline, post-completion of CRT, and one month following CRT. The proportions and absolute counts of CD3+CD4+ T cells in CR patients were distinctly higher than those in PR patients at the end of CRT, whereas the absolute counts of CD16+CD56+ NK cells were remarkably lower in CR patients compared to PR patients. The baseline proportion and absolute count of CD19+ B cells, as well as the absolute count of CD3+CD4+ T cells, were significantly higher in CR patients compared with PR patients.ConclusionCRT induced dynamic alterations in the peripheral lymphocyte profile of non-metastatic NPC patients. Assessing the variations in the distribution of circulating lymphocyte subsets among patients with different clinical treatment responses will be helpful in developing protocols for the concurrent utilization of immunotherapeutic drugs and CRT.